Depression and cardiovascular disease in elderly: Current understanding - Zhang, Yaxin; Chen, Yujing; Ma, Lina (Journal of clinical neuroscience, 2018)
•Cardiovascular diseases are accompanied by a high incidence of depression.•Depression can affect prognosis of patients with cardiovascular diseases.•Efforts should be made to improve patients’ psychological function. Geriatric depression is a major public health problem and has an especially large effect on health when comorbid with a chronic medical condition. Hypertension, coronary heart disease, and diabetes are accompanied by a high incidence of depression and can affect the treatment and prognosis. Depression is a highly prevalent risk factor for incident of and is associated with morbidity and mortality of cardiovascular disease. In addition to the proactive and effective control of primary diseases, efforts should also be made to improve patients’ psychological and social function. Current evidence on antidepressive therapy in patients with coronary diseases is limited. A better understanding of pathophysiological mechanisms underpinning depression and cardiovascular disease as well as the complex biological crosstalk of cardiovascular disease complicated with depression is particularly important for future therapeutic strategies. The following review is on current understanding of geriatric depression and cardiovascular disease.